(untitled) (Asian Journal of Social Science Studies, 2022)
Policy pilot is a unique policy experiment and innovation mechanism in China’s progressive reform. Since the reform and opening up, China’s economic and social development has benefited from the gradual development of policy pilots, and various policy pilots in the form of pilot projects and experimental zones have blossomed all over the country, whether in special economic zones or in the recently promoted pilot free trade zones, policy pilots have been an important way of innovation in local and regional governance. From policy pilot to system demonstration, the Shenzhen Pilot Demonstration Zone has assumed the important role of national strategic reform and leading reform. The launch and construction of the policy pilot to demonstration zone reflects both the governing resilience of the CPC and the governance resilience of the Chinese government, and also shows that the SEZ is a booster of the country’s transition from development to governance.